SEASONAL IMPACT ON COMB PRODUCTS OF LITTLE HONEY BEE, APIS FLOREA FARB (HYMENOPTERA - APIDAE) - JYOTI TIMANDE,; D. B. TEMBHARE, (The Bioscan, 2010)
The comb products, particularly, wax, honey and pollen of the little honey bee, Apis florea were analysed from the combs collected at ten different places in Wardha district (Maharashtra, State, India) during winter and summer seasons of the year 2003-2004. Content of these products per comb varies from one place to other and from summer season to winter. All comb products are found in higher quantity during winter than summer. The honey of Apis florea often unifloral and is characterised with a specific acidity, moisture, sugar and pollen content.